PKM di SMK Wira Harapan Kabupaten Badung Provinsi Bali: PKM in SMK Wira Harapan, Badung Regency, Bali Province - I Wayan Sumandya; I Wayan Eka Mahendra; Ni Nyoman Parmithi (FPMIPA IKIP PGRI Bali, 2019)
Wira Harapan Vocational School was established in 2008 on 4,500 m2 of land located on Jl, Raya Padang Luwih, Tegal Jaya Dalung, North Kuta District, Badung Regency, Bali Province. Wira Harapan Vocational School is supported by 60 teachers, consisting of permanent foundation teachers, contract teachers and honor teachers. Wira Harapan Vocational High School has 20 education staff consisting of permanent employees, contract employees and honorarium employees. In the 2017/2018 school year, Wira Harapan Vocational High School has 1.525 students, consisting of 522 class X students, 501 grade XI students, and 502 class XII students who are scattered into 42 study groups. The problem found in Wira Harapan Vocational School is the low understanding of teachers on electronic-based compilation in this PKM called E-module. The solution offered is to carry out workshops to improve teachers' understanding and skills regarding the procedures and mechanisms for the preparation of e-modules and mentoring (guided practice) is a follow-up to the workshop to improve teacher skills in preparing e-modules. The results achieved from this PKM activity are the increasing ability of teachers to prepare e-modules in accordance with the procedures for developing e-modules and the formulation of e-modules for each subject.